2006
DOI: 10.1111/j.0030-1299.2006.13379.x
|View full text |Cite
|
Sign up to set email alerts
|

On the indices of plant–plant competition and their pitfalls

Abstract: Oksanen, L., Sammul, M. and Mägi, M. 2006. On the indices of plant Á/plant competition and their pitfalls. Á/ Oikos 112: 149 Á/155. The index of relative competition intensity (RCI) has serious built-in biases, due to its asymptotic behavior when competition intensity is high and its tendency to obtain very low values when plants with neighbors intact perform better than neighbor removal plants. These biases have been partially corrected in the index of relative neighbor effect (RNE), but the existence of fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 16 publications
0
65
0
Order By: Relevance
“…The corrected index of relative competition intensity (CRCI; Oksanen et al 2006) of native species on average was significantly increased under elevated compared with ambient CO 2 , indicating that the competitive response of natives under elevated CO 2 was reduced. The CRCI is based on the competitive response of the target plant grown in competition with neighbors but can also be interpreted as a measure of the competitive effect of the neighbor plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The corrected index of relative competition intensity (CRCI; Oksanen et al 2006) of native species on average was significantly increased under elevated compared with ambient CO 2 , indicating that the competitive response of natives under elevated CO 2 was reduced. The CRCI is based on the competitive response of the target plant grown in competition with neighbors but can also be interpreted as a measure of the competitive effect of the neighbor plants.…”
Section: Discussionmentioning
confidence: 99%
“…For each species-pair, the competitive response of the target native and invasive exotic species was determined. There are a number of methods that have been developed to measure competitive ability, including the relative competition index (Grace 1995), relative neighbor effect (Markham and Chanway 1996) and logarithm of response ratio (Goldberg et al 1999), that have varying advantages and disadvantages (Goldberg et al 1999;Oksanen et al 2006). We chose to measure the corrected index of relative competition intensity (CRCI) following the method of Oksanen et al (2006).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the chemical agents used were not fully effective in relation to the above-mentioned species and they could occupy a part of the released ecological niche. Such phenomena of mutual competition and interspecific interactions between the components of segetal communities have been the object of research and have been confirmed in the studies of W e i n e r [17], W e i g e l t and J o l l i f f e [18], V i l et al [19], and O k s a n e n a et al [20]. Moreover, according to some authors, a single species occurring in high abundance exerts a greater negative effect on a cultivated plant than a multi-species community without clearly dominant species [21][22][23].…”
Section: Discussionmentioning
confidence: 84%
“…i) To explore the interaction among individual plants in the planting system, Relative Neighbor Effect (RNE) analysis was used based on equation from Markham and Chanway (1996) in Bachmann et al (2005), Oksanen et al (2006). RNE was calculated based on the sum of branches per plant and weight of kernel per plant per year, as follows:…”
Section: Nutmeg Plant Characteristicsmentioning
confidence: 99%